Maulana Tariq Jameel’s supplication for safety against COVID-19: A Pragmatic analysis - Shahid, Muhammad Ali; Mahmood, Anser (State institute of islamic studies salatiga, 2022)
Supplication, the symbol of man's humility, is at the core of all religions, with Allah regarded as the Supreme Being who listens to people's prayers and rewards them accordingly, regardless of religion. The purpose of this qualitative research is to look into the unique service provided by Maulana Tariq Jameel to God for protection from COVID-19, which is currently wreaking havoc on people's lives. On April 21, 2020, the program was broadcast live on the ARY News Channel's Shab-e- Meeraj programme, hosted by Waseem Badami, and was available to watch online. Devout Muslims from all over the world gathered for a specially organised 'Dua' to demonstrate their heartfelt humility and unwavering faith in Allah, who they believe will alleviate their deathly affliction as a result of their prayers. The video at https://www.youtube.com/watch?v=dSRuAo14NEI provided the data. The data was assessed using Aristotle's three modes of persuasion. The researchers paid close attention to the supplication during the study and coded the most relevant phrases before translating them from Urdu to English and analysed them from a pragmatic standpoint. The discussion section included references to prayers from a variety of religious traditions from various countries to integrate the study's findings. The study's findings show that when individuals, societies, or nations of any faith face a major calamity, they are more likely to be prone to Allah for protection than to other sources of protectionKeywords: Du’a, Persuasion, Religion, Staunch Faith, The sovereignty of Allah